2020
DOI: 10.1002/smtd.202000309
|View full text |Cite
|
Sign up to set email alerts
|

Development of Highly Efficient Dual‐AAV Split Adenosine Base Editor for In Vivo Gene Therapy

Abstract: The adenosine base editor (ABE) is able to catalyze A•T to C•G conversion efficiently and precisely in vivo, representing a new method for gene therapy. Adeno associated virus (AAV) is a well‐studied vector for gene delivery in vivo. However, due to the limited loading capacity of AAV vector (≈4800 bp), it is difficult to package ABE (≈5400 bp) into a single AAV. To tackle this problem, ABE can be split into two smaller parts through intein‐mediated protein trans‐splicing. Here, 14 different split sites of nCa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 63 publications
3
22
0
Order By: Relevance
“…Using the compact PE, we screened 4 split sites combined with Npu intein. Consistent with previous studies using base editors, we found split-cPE2-573 showed the highest on-target editing efficiency among split sites at endogenous loci 3,8,19 . Furthermore, we also found the compact PE without RNase H domain has no interaction with eRF1 which maintains the basal level of stop codon readthrough.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Using the compact PE, we screened 4 split sites combined with Npu intein. Consistent with previous studies using base editors, we found split-cPE2-573 showed the highest on-target editing efficiency among split sites at endogenous loci 3,8,19 . Furthermore, we also found the compact PE without RNase H domain has no interaction with eRF1 which maintains the basal level of stop codon readthrough.…”
Section: Discussionsupporting
confidence: 92%
“…(split-cPE2-637), Q674 (split-cPE2-674), or Q713 (split-cPE2-713) 3,8,19,20 . To determine the effect of each split site on cPE2 fusion, we co-transfected the N-terminal and C-terminal fragments of split-PE2 variants into HEK293T cells and measured protein expression using western blot.…”
Section: Development Of Efficient Split-pementioning
confidence: 99%
See 1 more Smart Citation
“…To this aim, a suitable in vivo delivery system, such as AAV or HDAd5/35++ adenovirus vectors should be used. So far, several studies have established a system to deliver in vivo ABEs or CBEs using AAV vectors (Winter et al, 2019 ; Chen et al, 2020 ; Hu et al, 2020 ; Levy et al, 2020 ). As BEs are large enzymes that cannot be packaged in a single AAV, many groups used a split-intein system based on the use of two AAV vectors harboring the two moieties of a SpCas9-based CBE fused to intein fragments that are reassembled in vivo via trans -splicing.…”
Section: Challenges Of Base Editing Approachesmentioning
confidence: 99%
“…In conventional genome editing, smaller CRISPR ortholog Staphylococcus aureus (Sa) Cas9 has led to the development of single AAV vector 12,13 , but adding a deaminase domain has been di cult 14 . Instead of composing a single AAV vector, the base editing components could be split into two AAV vectors to circumvent the size limitation 15 .…”
Section: Introductionmentioning
confidence: 99%